Preoperative rehabilitation in abdominal surgical oncology: the new standard for patient preparation for surgery? - Baušys, Augustinas; Maneikytė, Justė; Strupas, Kęstutis; Šakalienė, Ieva (Lietuvos chirurgija, 2019)
This paper shortly introduces preoperative rehabilitation as a new technique to prepare the patient for oncological surgery. First results of the clinical trials seem promising, because preoperative rehabilitation may increase the physical capacity of the patient, improve postoperative quality of life and even decrease the postoperative morbidity. Although, it remains unclear if preoperative rehabilitation could be beneficial before every surgery or only in case of major surgery. Therefore, before implication to the daily clinical practice, this new method has to be investigated in well designed clinical trials to determine the indications and to establish the optimized protocol of the preoperative rehabilitation.
Keywords: preoperative rehabilitation; surgical oncology; abdominal surgery